REDEFINING ASSESSMENT METHODS IN CHEMICAL ENGINEERING EDUCATION THROUGH AI-DRIVEN INNOVATIVE ASSESSMENT - Nurul Asyikin Md Zaki; Syafiza Abd Hashib; Ummi Kalthum Ibrahim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the integration of Artificial Intelligence (AI) tools in the assessment methods within chemical engineering education, specifically focusing on the Food Preservation Technology course at Universiti Teknologi MARA. Through a survey of 57 undergraduate students, this research explores the effectiveness of AI-assisted assessments in enhancing student engagement, understanding, and skill development. The results indicate that students find AI-assisted assessments significantly more engaging and effective than traditional methods, with high ratings for understanding complex concepts and developing critical thinking skills. However, concerns regarding academic integrity and ethical use of AI were also noted, suggesting a need for robust guidelines and continuous education to mitigate these risks. This study highlights the potential of AI tools to transform assessment practices in engineering education, promoting a balanced integration that maximizes benefits while addressing ethical considerations. The findings support the development of a comprehensive framework for the ethical and effective use of AI in educational assessments, ultimately aiming to produce well-rounded engineers equipped with both theoretical knowledge and practical expertise.